Implementation of nursing-led follow-up service for patients newly discharged from paediatric intensive care units: quality improvement initiative - Mohannad Antar; Ruqiah Ali AlZaher; Iris Murabi; Jaber Enazi; Efraim Kolobe; Shelia Delafuente; Mona Awani (BMJ Open Quality)
Background Human resource shortages are a global challenge in the healthcare system and create barriers in providing timely follow-up visits for paediatric patients discharged recently from the intensive care unit (ICU). Relying on experienced intensive care nurses to provide follow-up services for patients post paediatric ICU (PICU) transfer has been proven a cost-effective and safe practice. This study aimed to achieve no delays in initiating follow-up visits and to assess the safety of implementing a nurse-led follow-up service.Methods Plan–Do–Study–Act cycle was used targeting to achieve no delay in initiating follow-up visits and to maintain the safety of the patients. This cycle resulted in the implementation of a nurse-led follow-up service, which is under the provision of a paediatric rapid response team (RRT). Fifteen PICU nurses were trained in their new roles and responsibilities. Service databases were established to track and trend the frequency of visits, service safety measures and clinical deterioration.Results After the implementation of the nurse-led follow-up service, we achieved no delays in initiating the follow-up visits. 45% (n=487) of patients received a nurse-led follow-up visit service. Safety measures demonstrated 0.21% (n=1) recorded events of RRT activations during the follow-up service. RRT activation within 48 hours from service discharge was 1.2% (n=6), and readmission to PICU within 48 hours was 0.8% (n=4). No cardiopulmonary arrest event was recorded for patients under the nurse-led follow-up service during the service, postservice discharge or postreadmission to PICU.Conclusions Implementing nursing-led service has been shown to be safe, efficient and provides patients with timely visits post-PICU discharge.